A indeterminação do conceito da essencialidade tributária e o impacto na dignidade menstrual: desvendando o desafio da tributação de absorventes higiênicos e a luta pelo reconhecimento da essencialidade - Josilaine Martins Santos (2024)
This dissertation addresses the complexity and indeterminacy of the concept of tax essentiality in the Brazilian context, with a specific focus on the taxation of sanitary pads and their relationship with female dignity. The research explores how the lack of a clear definition of "essentiality" in the Brazilian tax system contributes to challenges in implementing fair fiscal policies, particularly those that directly affect women's health and well-being. Through a critical analysis of legislation, jurisprudence, and specific tax norms, this study highlights the discrepancy between the biological necessity of sanitary pads and their often non-essential classification, which imposes an unfair and disproportionate tax burden on women over time. The dissertation proposes a dialogue between the theory of tax justice, gender equality, and human rights, arguing that recognizing the essentiality of sanitary pads is a fundamental step towards promoting female dignity and fiscal equity.